2015
DOI: 10.1242/dev.122184
|View full text |Cite
|
Sign up to set email alerts
|

Female-to-male sex reversal in mice caused by transgenic overexpression of Dmrt1

Abstract: Genes related to Dmrt1, which encodes a DNA-binding DM domain transcription factor, act as triggers for primary sex determination in a broad range of metazoan species. However, this role is fulfilled in mammals by Sry, a newly evolved gene on the Y chromosome, such that Dmrt1 has become dispensable for primary sex determination and instead maintains Sertoli cell phenotype in postnatal testes. Here, we report that enforced expression of Dmrt1 in XX mouse fetal gonads using a Wt1-BAC transgene system is sufficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 39 publications
1
61
0
2
Order By: Relevance
“…In female mice, transgenic overexpression of Dmrt1 in somatic gonadal cells causes transdifferentiation of adult granulosa cells to Sertoli cells, which indicates that DMRT1 is sufficient to convert fully differentiated female somatic cells into functional male somatic cells. Interestingly, this somatic sex conversion does not depend on the male sex determinant SOX9 (Lindeman et al, 2015;Zhao et al, 2015). Similarly, in adult Drosophila females, we have found that ectopic expression of chinmo masculinizes the ovary independently of the male sex determinant Dsx M .…”
Section: Discussionmentioning
confidence: 53%
“…In female mice, transgenic overexpression of Dmrt1 in somatic gonadal cells causes transdifferentiation of adult granulosa cells to Sertoli cells, which indicates that DMRT1 is sufficient to convert fully differentiated female somatic cells into functional male somatic cells. Interestingly, this somatic sex conversion does not depend on the male sex determinant SOX9 (Lindeman et al, 2015;Zhao et al, 2015). Similarly, in adult Drosophila females, we have found that ectopic expression of chinmo masculinizes the ovary independently of the male sex determinant Dsx M .…”
Section: Discussionmentioning
confidence: 53%
“…Although no SRY -negative 46,XX DSD patients with testicular tissue and DMRT1 overexpression have as yet been identified, increased expression of Dmrt1 in the foetal gonads of transgenic XX mice is sufficient to drive testicular differentiation and male sex development [Zhao et al, 2015].…”
Section: Dmrt1mentioning
confidence: 99%
“…Studies of compound mutant mice, lacking both Dmrt1 and pro-ovary genes such as Foxl2, suggest that DMRT1 acts to prevent retinoic acid (RA)-dependent reprogramming of Sertoli cells in the postnatal testis, allowing Sertoli cells to utilize RA signaling to support germ cell development (Minkina et al 2014). However, notwithstanding its role in Sertoli cell fate maintenance, recent experiments in which Dmrt1 is overexpressed in the mouse XX embryonic gonad, resulting in Sertoli cell development, indicate that the potential to respond to DMRT1 at the primary sex-determining stage still exists in the mouse genome (Lindeman et al 2015;Zhao et al 2015). The situation in humans is just as unclear.…”
Section: Molecules Of Unclear Significance: Dmrt1 and Dax1mentioning
confidence: 99%